Targeting site-specific N-glycosylated B7H3 induces potent antitumor immunity - Huang, Yun; Zhong, Wen-Qing; Yang, Xiao-Yu; Shan, Jia-Lu; Zhou, Ling; Li, Zhi-Ling; Guo, Yi-Qing; Zhang, Kai-Ming; Du, Tian; Zhang, Hai-Liang; Hu, Bing-Xin; Chen, Yu-Hong; et al. (Nature communications, 2025)
B7H3, an immune checkpoint molecule, is a highly N-glycosylated membrane protein. However, the key glycosylated asparagine residues that mediate the function of the B7H3 protein are still unclear. Here we identify that N-glycans attached to asparagine residues N91/309 and N104/322 are required for proper B7H3 localization on the cell surface membrane. We demonstrate that mutations in these two pairs of N-glycosylation sites induce ER accumulation of B7H3 by blocking its ER-to-Golgi translocation and subsequently promote its degradation via the endoplasmic reticulum-associated protein degradation pathway. Additional evidence suggests that N-glycosylation at N91/309 and N104/322 of B7H3 is essential for its inhibition of T-cell proliferation and activation. More importantly, a monoclonal antibody, Ab-82, preferentially targeting B7H3 glycosylated at N91/309 and N104/322 is developed, which exhibits the ability to elicit cytotoxic T lymphocyte-mediated antitumor immunity via B7H3 internalization. Together, these findings offer a rationale for targeting glycosylated B7H3 as a potential strategy for immunotherapy. Glycosylated asparagine residues that mediate the function of the B7H3 protein are unclear. Here the authors identify the important N-glycosylation sites for B7H3 cell surface localization and T cell inhibition, followed by the development of N91/309 and N104/322 preferentially targeting monoclonal antibody manifesting enhanced antitumor immunity.